UMP is 97th among world’s greenest varsities - UMP, PNC (2019)
KUANTAN: Universiti Malaysia Pahang (UMP) has improved its ranking on the world stage, moving to 97, from its 107th position, in the UI (University of Indonesia)-GreenMetric World University Ranking for 2017.